Cocos nucifera l. (coir) fiber application as a filler and its effect on the volumetric shrinkage of flowable composite resin: an in vitro study - cevanti, Twi agnita; Tameno, Yolanda Agustina; Mawarani, Lizda Johar; Akwan, Yulie Emilda; Prananingrum, Widyasri; Son, Meekyoung (Padjadjaran Journal of Dentistry, 2025)
Introduction: The use of composite resin as a restorative material has the disadvantage of experiencing volumetric shrinkage during polymerization, which can lead to restoration failure. Fiber-reinforced composites can reduce volumetric shrinkage in restorative materials. Coir fiber has the potential to replace synthetic fillers because its hollow fiber structure resembles foam, supporting a compact yet lightweight structure. This characteristic is expected to reduce the volumetric shrinkage of composite resin. This study aims to analyze the effect of coir fiber application as a filler on flowable composite resin on shrinkage, comparing it with flowable composite resin containing synthetic filler. Methods: The cellulose fiber used as a filler was synthesized from coir, while the matrix consisted of BisGMA and TEGDMA resins in a ratio 5:1. The composite was prepared with a coir fiber-to-matrix resin composition of 70:30, and polymerization was carried out by irradiation for 40 seconds. Volumetric shrinkage was tested 90 minutes after irradiation. The dimensions of the composite sample were measured from images captured using a digital microscope and analyzed with ImageJ software. The volume shrinkage was then calculated based on these dimensions. Shrinkage was further confirmed through SEM analysis of marginal adaptation tests. Results: The application of coir fiber as a filler effectively reduced the volumetric shrinkage of the composite compared to the composites with synthetic filler. Statistical analyses using the Mann-Whitney test results indicated that the type of filler in flowable composite resin had a significant effect, with a p-value of 0.047 (p<0.05). Conclusion: Application of coconut fiber as filler in flowable composite resin significantly reduce volumetric shrinkage, making it three times smaller than that of flowable composite resin with a synthetic filler.